2018
DOI: 10.1089/neu.2017.5365
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Functional Connectivity in Adults with Persistent Post-Concussion Symptoms: A Functional Near-Infrared Spectroscopy Study

Abstract: Concussion, or mild traumatic brain injury (mTBI), accounts for ∼80% of all TBIs across North America. The majority of mTBI patients recover within days to weeks; however, 14–36% of the time, acute mTBI symptoms persist for months or even years and develop into persistent post-concussion symptoms (PPCS). There is a need to find biomarkers in patients with PPCS, to improve prognostic ability and to provide insight into the pathophysiology underlying chronic symptoms. Recent research has pointed toward impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 62 publications
(80 reference statements)
6
53
0
1
Order By: Relevance
“…We found that patients with PBC exhibit significantly reduced cortical hemodynamic coherence (Fig. ), similar in magnitude to reductions we have previously reported in adults with MS and in adults and children with chronic symptoms following mild traumatic brain injury . In particular, our findings of reduced coherence were greatest for frequencies centered around the ~0.1‐Hz oscillation (10‐second rhythm) known as the “Mayer wave,” indicating altered vasomotor regulation of cerebral blood flow .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that patients with PBC exhibit significantly reduced cortical hemodynamic coherence (Fig. ), similar in magnitude to reductions we have previously reported in adults with MS and in adults and children with chronic symptoms following mild traumatic brain injury . In particular, our findings of reduced coherence were greatest for frequencies centered around the ~0.1‐Hz oscillation (10‐second rhythm) known as the “Mayer wave,” indicating altered vasomotor regulation of cerebral blood flow .…”
Section: Discussionsupporting
confidence: 87%
“…2), similar in magnitude to reductions we have previously reported in adults with MS (6) and in adults and children with chronic symptoms following mild traumatic brain injury. (33,34) In particular, our findings of reduced coherence were greatest for frequencies centered around the ~0.1-Hz oscillation (10-second rhythm) known as the "Mayer wave," indicating altered vasomotor regulation of cerebral blood flow. (22) Dysregulation of cerebral blood flow and perfusion in these patients may result from two potential mechanisms: (1) disrupted efferent sympathetic nervous control of arterial blood pressure and/or (2) direct damage or injury to the vascular endothelial cells, both of which may cause dysfunctional vasomotor activity.…”
Section: Resting-state Hemodynamic Coherencementioning
confidence: 73%
“…Thus, it has the potential to be used to examine several physiological mechanisms including NVC (Ellis et al, 2016;Epps and Allen, 2017). Few studies have used fNIRS for the assessment and monitoring of post-concussive injury (Urban et al, 2015;Bishop and Neary, 2018;Hocke et al, 2018). Relative changes were observed over time with O 2 Hb decreasing after the initial concussion injury and HHb increasing until day 14 post-injury.…”
Section: Introductionmentioning
confidence: 99%
“…294 Compared to healthy persons, the patients with mild TBI also showed lower functional connectivity that was inversely linked with impairment intensity, and the di®erence in connectivity was more pronounced during the task period as compared to the resting state. 295…”
Section: Hand/¯nger Movement Taskmentioning
confidence: 99%
“…[30][31][32][33][34]79,121,236,266,272 Functional and e®ective connectivity analyses are useful to understand the processing that takes place in the human brain, and covering more brain areas will allow for better understanding based on the experimental conditions. 4,271,[295][296][297]352 The bundled optode approach that creates hundreds of channels at di®erent brain depths with high spatial resolution can assuredly assist in the creation of 3D images via fNIRS, which can be compared with those created via fMRI. 7 This technique involves spatially resolved spectroscopy that utilizes multidistance channel formation among groups of sources and detectors placed as close to each other as possible.…”
Section: Channel Resolution and Limitationmentioning
confidence: 99%